2013
DOI: 10.1186/1752-2897-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of the use and costs of routine chest x rays in a trauma setting

Abstract: IntroductionChest x-rays (CXR) are routinely obtained on blunt trauma patients. Many patients also receive additional imaging with thoracic computed tomography scans for other indications. We hypothesized that in hemodynamically normal, awake and alert blunt trauma patients, CXR can be deferred in those who will also receive a TCT with significant cost savings.MethodsWe retrospectively reviewed the charts of trauma patients from 1/1/2010 to 12/31/2010 who received both a CXR and TCT in the trauma room. Billing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
(22 reference statements)
0
18
1
Order By: Relevance
“…Five activities were identified to determine the estimated cost. These included human resources, capital, consumables, energy cost, and radiologist fee for study interpretation [6][7][8] (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five activities were identified to determine the estimated cost. These included human resources, capital, consumables, energy cost, and radiologist fee for study interpretation [6][7][8] (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Medical facilities need to calculate utilizing their ABCA estimation to determine facility-based cost for a single chest radiograph. [6][7][8] In particular, smaller facilities where chest radiographs are part of a radiology business model and could have a higher effect. From a purely financial perspective this may affect net revenue.…”
Section: Financial Considerationsmentioning
confidence: 99%
“…Others studies reported the sensitivities of 29% [10] and 14.3% [9] in detecting pneumothorax. In the present study, the sensitivity of CXR was 55.3% and 33% in detecting rib fractures and pneumothoraces respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported sensitivities of 25.5% [8] and 39.4% [9] for CXR in detecting rib fractures in patients with blunt chest trauma. Others studies reported the sensitivities of 29% [10] and 14.3% [9] in detecting pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…20 Median charges for chest x-ray in 2013 are $298 per examination, while median charges for chest CT are $3,294 per patient. 13,21 Potential risks include harmful effects from ionizing radiation exposure, as well as potential renal injury and allergic reactions from intravenous contrast. 22 While CXR delivers negligible amounts of radiation, chest CT exposes the patient to a considerable effective radiation dose (ERD) and cancer induction risk, especially for women.…”
Section: Introductionmentioning
confidence: 99%